Domesticating Spaces in Transition: Politics and Practices in the Gender and Development Literature, 1970-99 - Phillips, Lynne; Ilcan, Suzan (Anthropologica, 2022)
Much of how we understand cultural transformation in local and global economies is influenced by a spatiality that directs or governs people's lives and their places of transition. In this article, we employ the concept of "spatial domestication" to interrogate notions of gender and development as they have been predominantly conceptualized in the gender and development literature over the last 30 years. While we argue that this literature contains unexamined spatial dimensions and assumptions, we demonstrate that notions of space are, and have been, crucial to the construction of both "gender" and "development" in particular modernization, dependency, and knowledge/power approaches. Our examination of this literature suggests that the question of how space is, and has been, domesticated may constitute an essential future direction for the discipline of anthropology